Low-cost synthesis of pure ZnO nanowalls showing three-fold symmetry. (13th February 2018) - Scuderi, Mario; Strano, Vincenzina; Spinella, Corrado; Nicotra, Giuseppe; Mirabella, Salvo
Abstract: ZnO nanowalls (NWLs) represent a non-toxic, Earth abundant, high surface-to-volume ratio, semiconducting nanostructure which has already showed potential applications in biosensing, environmental monitoring and energy. Low-cost synthesis of these nanostructures is extremely appealing for large scale upgrading of laboratory results, and its implementation has to be tested at the nanoscale, at least in terms of chemical purity and crystallographic orientation. Here, we have produced pure and texturized ZnO NWLs by using chemical bath deposition (CBD) synthesis followed by a thermal treatment at 300 °C. We examined the NWL formation process and the new obtained structure at the nanoscale, by means of scanning and transmission electron microscopy in combination with x-ray diffraction and Rutherford backscattering spectrometry. We have shown that only after annealing at 300 °C in nitrogen does the as-grown material, composed of a mixture of Zn compounds NWLs, show its peculiar crystal arrangement. The resulting ZnO sheets are in fact made by ZnO wurtzite domains (4–5 nm) that show a particular kind of texturization; indeed, they are aligned with their own c -axis always perpendicular to the sheets forming the wall and rotated (around the c -axis) by multiples of 20° from each other. The presented data show that low-cost CBD, followed by an annealing process, gives pure ZnO with a peculiarly ordered nanostructure that shows three-fold symmetry. Such evidence at the nanoscale will have significant implications for realizing sensing or catalyst devices based on ZnO NWLs.